2016
DOI: 10.1007/s00125-016-4150-x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide serum markers in islet autoantibody-positive children

Abstract: Aims/hypothesis We sought to identify minimal sets of serum peptide signatures as markers for islet autoimmunity and predictors of progression rates to clinical type 1 diabetes in a case-control study. Methods A double cross-validation approach was applied to first prioritise peptides from a shotgun proteomic approach in 45 islet autoantibody-positive and -negative children from the BABYDIAB/BABYDIET birth cohorts. Targeted proteomics for 82 discriminating peptides were then applied to samples from another 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 44 publications
2
34
0
2
Order By: Relevance
“…Longitudinal samples, collected from birth to the appearance of autoantibodies and clinical type 1 diabetes diagnosis, have enabled the discovery of innate and adaptive immunity-related transcriptome signatures before seroconversion. [28,39,40] Also, recent studies have reported serum proteomes as indicators of disease progression in individuals with type 1 diabetes, during various stages of the disease, from early infancy to seroconversion and diagnosis [41][42][43]. In such studies, special attention should be given to the selection of adequate reference samples as age has a profound effect on the proteome, especially during early childhood [44][45][46].…”
Section: Emerging Biomarkers: Omicsmentioning
confidence: 99%
“…Longitudinal samples, collected from birth to the appearance of autoantibodies and clinical type 1 diabetes diagnosis, have enabled the discovery of innate and adaptive immunity-related transcriptome signatures before seroconversion. [28,39,40] Also, recent studies have reported serum proteomes as indicators of disease progression in individuals with type 1 diabetes, during various stages of the disease, from early infancy to seroconversion and diagnosis [41][42][43]. In such studies, special attention should be given to the selection of adequate reference samples as age has a profound effect on the proteome, especially during early childhood [44][45][46].…”
Section: Emerging Biomarkers: Omicsmentioning
confidence: 99%
“…Christine von Toerne in the study of 45 islet auto-antibody-positive and -negative children from the BABYDIAB/BABYDIET birth cohorts performed a proteomic analysis [17]. Two peptides (from apolipoprotein M and apolipoprotein C-IV) were sufficient to discriminate between auto-antibody-positive and auto-antibody-negative children.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified markers of β-cell dysfunction and new onset of T1D in human urine and blood plasma or serum [68][69][70][71]. A proteomic analysis of urine from children with T1D showed a consistent increase of several lysosomal enzymes [72], which was validated in a second cohort [73].…”
Section: Linking Pathways Of β-Cell Dysfunction To Biomarker Developmentmentioning
confidence: 91%
“…Release of lysosomal enzymes is a process associated with inflammation, which in this case could be a consequence of the damage to the renal tubular epithelial cells caused by chronic hyperglycemia [72,73]. Proteins related to inflammation and other innate immune response processes are commonly found as blood biomarkers of islet autoimmunity and T1D onset [68][69][70][71]. While a number of biomarker candidates have been reported from recent literature [74], most of them are present in plasma in mid to high abundances, but not necessarily being directly derived from β cells.…”
Section: Linking Pathways Of β-Cell Dysfunction To Biomarker Developmentmentioning
confidence: 99%